Synthesis and optical band gap investigation of PVA/CdS nanocomposite films - Abdullah, Omed Gh. (Sulaimani Journal for Pure and Applied Sciences, 2015)
The nanocomposites of polyvinyl alcohol PVA with different concentration of cadmium sulfide nanoparticles CdS-NPs were obtained using chemical reduction route and casting technique. The effects of CdS concentrations on the optical properties of the PVA films were studied in the regions near-infrared, ultraviolet, and visible wavelength, (190-1100) nm. The obtained optical parameters were found to be strongly affected by CdS contents. From the derivation of Tauc's relation, it was found that the direct allowed transition was more probable in both CdS/PVA nanocomposite and CdS-NP. The results indicate that the obtained values of optical absorption edge and energies band gap decreases with increasing salt contents, as well as the reduction of the width of the tail localized states was observed. The study has been also extended to include the estimating of CdS particle size from the energies band gap for the investigated nanocomposite films.
Keywords: Nanocomposite CdS nanoparticle optical band gaps particle size